Can analytical psychology be applied to the therapeutic community?. Issue 3 (2nd October 2020) - Howe, Andrew John
Abstract : Purpose: The purpose of this paper is to investigate the theoretical potential of applying Jungian/analytical psychology concepts to a contemporary therapeutic community (TC) within the national health service. Design/methodology/approach: A literature review concerning a Jungian understanding of group psychotherapy and TCs was undertaken. A summary and discussion of a detailed written account of a previous Jungian TC was then conducted. A comparison between a modern-day TC and Jungian approaches was then conducted with an ending discussion on the feasibility of incorporating Jungian ideas into modern work. Findings: While Jung is thought to have a wholly negative view of groups and group psychotherapy, this was not found in the case. Furthermore, post-Jungian authors have attempted to use ideas from analytical psychology in their group work. While there are some aspects that could be implemented with relative ease in the modern TC, a complete shift into this different way of working would be a challenge and its current evidence base would not support this. Originality/value: To the best of author's knowledge, there are no other academic papers that have considered this subject.